Taco Bell Corporation : public perception and brand protection (A) - Hall, Jared T.; Viola, Michael P.; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Fears regarding the introduction of genetically modified foods into the commercial food market have grown steadily since the mid-1990s. In the autumn of 2000, Taco Bell Corporation found itself caught between Friends of the Earth, a not-for-profit environmental advocacy group, and Kraft Foods Corporation, a business partner that manufactured and marketed grocery store products under the Taco Bell brand name. When environmental advocates claimed that genetically modified corn had somehow found its way into Taco Bell corn tortillas manufactured by Kraft, both companies were faced with important accusations about food safety and threats to brand image.
Originally published: Hall, J. T., Viola, M. P., & ORourke, J. S. (2003). Taco Bell Corporation: Public perception and brand protection (A). 03-07 (A). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Taco Bell (Firm) -- Public opinion; Kraft Heinz Company; Fast food restaurants -- Health aspects; Food -- Safety measures; Corporate image